ANALYSE DES CONTRAINTES DE VIABILITE DE LA VEGETATION URBAINE : CAS DES ARBRES D’ALIGNEMENT DANS LA VILLE DE PORTO-NOVO AU BENIN - Aziz, Osseni Abdel; Brice, Sinsin; Ismaïla, Toko Imorou (European Scientific Journal, ESJ, 2014)
Many efforts have been made in recent decades to provide urban forestry a tool of conservation plantre sources and sustainable development of cities. In southern countries, these efforts are more focused on conventional reforestation and education without much considers the factors that determine the survival of the trees.This study on the Porto-Novo city in Bénin, is a better understanding of the viability of urban trees, including those planted by analyzing the constraints of the medium. Lands atimages were used to determine state changes in vegetation cover in 2003 and 2013 An inventory of forms of mutilation on the trees is associated with a survey of populations to link the urban practices and their causes on the viability of urban trees. For data processing, normalized vegetation index is calculated in ENVI5 and mapped in ArcGIS10. Chi Square test and correspondence analysisare performed under R. The results show a decline in the normal state and moderate vegetation and an increase in stress states and mineral areas. Depending on the population, it is the anthropogenic activities (P= 0.001) and planning conditions (P= 0.01), which are currently the factors significant constraint strees. The consequences are biologically and landscape esthetically. The inclusion of such information is necessary for a better future of urban forestry in the city.